IMPLEMENTASI PROGRAM PELATIHAN - Mori, Riffati Hikmi; Amelia, Leni; Eisyah Agisti, Neyza Nur; Bachtiar, Machdum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the implementation of a training program designed to enhance human resource competencies and organizational performance. The analysis focuses on the stages of preparation, execution, evaluation, as well as monitoring and supervision within the training management cycle. A qualitative approach was employed, utilizing observation, interviews, and documentation as data collection techniques. The findings indicate that the training implementation began with a systematic identification of competency gaps, followed by program design based on Training Need Analysis (TNA) and Developmental Need Analysis (DNA). The implementation phase was carried out in a structured manner through a combination of lectures, discussions, and practical sessions accompanied by intensive mentoring. Evaluation activities were conducted to measure the effectiveness of the program in improving participants’ skills, while continuous monitoring ensured alignment with organizational standards and objectives. Although several technical challenges and limitations in internal trainer availability were identified, the overall training program contributed positively to competency development and supported the achievement of organizational strategic goals.